Arabic-Chinese and English Relay Translation (1970-2020): A Historiographical Bibliometric Study - Xiang, Luxi (2022)
A Master of Arts thesis in English/Arabic/English Translation and Interpreting (MATI) by Luxi Xiang entitled, “Arabic-Chinese and English Relay Translation (1970-2020): A Historiographical Bibliometric Study”, submitted in April 2022. Thesis advisor is Dr. Said Faiq. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).